PERFORMANCE DETERMINANTS OF THE INSURANCE COMPANY’S ACTIVITY - LOM, Ionut; MARIN, Lilian (Economy and Sociology, 2021)
Considering the growing role of the insurance protection function in a dynamic business environment, the issue of efficient management and solvency of insurance companies is becoming a priority. The purpose of this study is to identify the performance determinants of the insurance business. To achieve this goal, the authors researched methodological aspects of assessing the financial performance of the insurance company in terms of absolute and relative indicators of financial results. The authors consider that profit and profitability indicators are important to give a quantitative and qualitative assessment to the financial management of companies. The monographic method and the causal explanation were applied to concretize the model for forming the overall financial result of the insurance company. The methodological approach in order to test the hypothesis was made by adapting the factorial model for analysing the profitability of sales revenues to the specifics of the insurance company’s activity. Profit and profitability indicators play an important role in the process of qualitative and quantitative evaluation of the company’s financial management. The analyses performed by the authors based on the public financial statements of the insurance company “Acord Grup” SA, the reports of the National Financial Market Commission (NCFM) and the reports of the Romanian Financial Supervisory Authority (FSA) highlighted the decreasing trend of profitability indicators of insurance companies. In order to react as quickly as possible and manage the given situation, the authors recommend to the managers of the insurance companies to apply the factorial analysis models, in order to capture the determinants of the profitability indicators of the insurance activity, which require an increased attention.